1997
DOI: 10.1051/mmm:1997131
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Induced Structural Modification of the Oxidized Silicon Micro-Clusters in ZnO Matrix

Abstract: Abstract. 2014 Si/ZnO nano-and micro-composites were grown on SiO2 glass substrates by co-sputtering technique. The content of Si in the films was controlled by the no. of Si pieces placed on the ZnO target. The crystallinity of the composite films decreased on increasing the Si content in them and increased on post deposition thermal annealing. The dispersed Si in the ZnO matrix remained in the form of nano-particles with an average size value of 3.7 nm and does not depend on the fractional Si content in them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…We observed that the dielectric response (〈⑀ 1 〉 and 〈⑀ 2 〉) of the as-deposited films presents a broad band above 3.5 eV, characteristic of an amorphous phase of the ZnO matrix. These results agree with the XRD analysis of the Si/ZnO composite films reported by Pal et al 11 On incorporation of Si in the matrix, the band became more intense and shifted toward higher energy. The increase of intensity of the band and its broadness might be due to the increase of amorphous phase of the martix on incorporation of Si in the films.…”
Section: Optical Characterizationsupporting
confidence: 95%
“…We observed that the dielectric response (〈⑀ 1 〉 and 〈⑀ 2 〉) of the as-deposited films presents a broad band above 3.5 eV, characteristic of an amorphous phase of the ZnO matrix. These results agree with the XRD analysis of the Si/ZnO composite films reported by Pal et al 11 On incorporation of Si in the matrix, the band became more intense and shifted toward higher energy. The increase of intensity of the band and its broadness might be due to the increase of amorphous phase of the martix on incorporation of Si in the films.…”
Section: Optical Characterizationsupporting
confidence: 95%
“…In fact, such a reduction of crystallinity on doping of metals/semiconductors has been observed even in sputter-deposited composite films. 18,19 The reduction of crystallinity in the samples was further monitored by measuring the average particle size in the samples from the ͑002͒ diffraction peaks using the Scherrer formula:…”
Section: A Structure Morphology and Compositionmentioning
confidence: 99%
“…Thus it becomes clear that the compositional ratio of ZnO to Silicon which inturn means the neighbourhood offered to ZnO nanoparticles is deterimental in bringing desired changes in optical properties of the nanocomposites and should be given its due concern. Nanocomposites based on ZnO and Si have been fabricated by sol gel [15,16,17,18,19], RF sputtering [20,21,22,23], pulsed laser deposition [24], via chemical routes [25,26,27,28], reverse micelle method [29]and their optical properties studied. These research calls for more systematic work to optimize the parameteres for tailoring the properties and for a better understanding of interface and defect mechanism of ZnO:Si nanocomposites Hence to this effect, we have started systematic study of Zinc Oxide grains in nano regime embedded in amorphous Silicon matrix.…”
Section: Introductionmentioning
confidence: 99%